Multiple liver masses mimicking metastatic liver disease in an elderly patient - Köklü, Hayretdin; Armağan, Berkan; Karadağ, Ömer; Karcaaltıncaba, Musturay; Özgen Kıratlı, Müzeyyen Pınar; Gedikoğlu, Gökhan; Kav, Taylan (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Köklü H, Armağan B, Karadağ Ö, et al. Multiple liver masses mimicking metastatic liver disease in an elderly patient. Turk J Gastroenterol 2018; 29: 115-8.